fMRI-guided rTMS in the treatment of auditory verbal hallucinations in schizophrenia: a case report - Aytulun, Aykut; Brouzou, Katia; Campana, Mattia; Aliakbari, Navid; Pessanha-Schlegel, Francesca; Faustmann, Timo Jendrik; Kujovic, Milenko; Kamp, Daniel; Lahnakoski, Juha M.; Schilbach, Leonhard (Frontiers in Psychiatry, 2026)
Auditory verbal hallucinations (AVH) are a core symptom of schizophrenia and contribute substantially to patient suffering and disability. They are among the most persistent symptoms and do not respond to medication in a substantial portion of patients. Here, we report the application of task-based functional magnetic resonance imaging (fMRI)-guided repetitive transcranial magnetic stimulation (rTMS) in a patient with treatment-resistant AVH. An individualized stimulation target was identified in the left temporal cortex near Heschl’s gyrus using a validated fMRI task. Over a period of 18 months, the patient underwent three cycles of inhibitory 1 Hz rTMS of this target. As a result, AVH severity decreased by 33% and the global symptom score improved by 40%. Functional connectivity analyses revealed an increase in coupling between the temporal target seed and a fronto-cingulate-insular network that has been implicated in reality and performance monitoring. This case highlights the potential of fMRI-guided rTMS as a personalized neuromodulatory therapy for refractory AVH in schizophrenia, warranting further systematic investigation.